2012
DOI: 10.1080/08952833.2012.631862
|View full text |Cite
|
Sign up to set email alerts
|

Calculating All of Our Losses: Writing Real-World Therapy Experiences in Child Welfare

Abstract: In the child welfare system, child maltreatment prevention and intervention are of primary focus. Yet when working from a multi--systems perspective, both the child and parent systems are of vital importance while aligning with caseworkers goals, and adhering to court orders in a larger community context. Although we adhere to a strengths-based perspective, the systemic narrative of trauma takes precedence over certain progressions within family life. As a result, we provide an autoethnographic account of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…By taking an eco-developmental perspective (Bronfenbrenner, 2005), we were able to organize our data to demonstrate how looking across the lifespan provides better insights into the trajectories of these women's lives. Each participant had suffered from childhood sexual abuse, sexual assault, and interpersonal partner violence (Reid-Cunningham, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By taking an eco-developmental perspective (Bronfenbrenner, 2005), we were able to organize our data to demonstrate how looking across the lifespan provides better insights into the trajectories of these women's lives. Each participant had suffered from childhood sexual abuse, sexual assault, and interpersonal partner violence (Reid-Cunningham, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We also wanted to understand women's experiences interacting with multiple systems in the context of their ongoing development, negatively affected by complex trauma. Thus, in addition to a critical feminist, we incorporated an eco-developmental lens (Bronfenbrenner, 2005;McDowell & Fang, 2007) in order to effectively comprehend the contextual intricacies and the intersectional stigma suffered by women experiencing long-term detrimental health outcomes as survivors of complex trauma. This approach responds to the need posed by Bowleg (2012) in reference to using intersectionality as a consolidating framework for issues related to public health for populations exposed to disadvantaging social structures.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Eleven primary challenges were evident in the data and were found to exist across three distinguishable, yet interrelated levels: system, agency, and client. Challenges at the intersection of child welfare and mental and behavioral health have been noted in other studies, 15,17,18,20 but rarely using qualitative focus groups with TSPs themselves to give voice to their experiences. Therefore, this study deepens knowledge of challenges from the perspective of this key stakeholder group and findings suggest numerous implications.…”
Section: Implications For Behavioral Healthmentioning
confidence: 93%
“…Existing contributions in this area include an autoethnographic narrative of child welfare-focused therapists by Burns-Jager and colleagues in 2012 in which they highlight that families have complex situations in which no outcome may be seen as best and that they struggled as therapeutic providers to accept different forms of outcomes, such as the termination of a client's parental rights. 20 Shea's 2015 online survey with therapeutic providers delivering attachment-based treatment to children in foster care found that they experience similar feelings of helplessness and hopelessness as the children they are serving, being without a significant sense of control within the system. 21 Another study in Washington state involved interviews with child welfare caseworkers, but also engaged therapeutic providers through surveys.…”
Section: Introductionmentioning
confidence: 99%